1989
DOI: 10.1007/bf00016024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light on accumulation of photosynthesis-specific transcripts in the cyanobacterium Synechocystis 6803

Abstract: Transcript accumulation for the psbA, psbD, psbD-C, rbcL-S and rrn genes in Synechocystis 6803 was followed under different light conditions. psbA, psbD, psbD-C and rbcL-S transcripts required light to accumulate and the relative abundance of these transcripts differed between high and low light conditions. Under high light conditions, steady-state levels of psbA, psbD and psbD-C transcripts were higher while levels of rbcL-S transcripts were lower than under low light conditions. rrn transcripts accumulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
245
0
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(269 citation statements)
references
References 31 publications
(47 reference statements)
18
245
0
2
Order By: Relevance
“…Expression analyses have led us to conclude Jansson, 1989,1991;Mohamed et al, 1993) that the -35 and -10 motifs of psbA2 constitute a strong light-inducible promoter in Synechocystis sp 6803. No expression of thepsbA7 gene has been detected (Mohamed and Jansson, 1989), and alignment of the upstream regions of-the three psbA genes (Figure 2) has shown that the two putative psbA 7 promoters (Osiewacz and Mclntosh, 1987;Mohamed et al, 1993;Nixon and Jansson, 1996) differ significantly from the psbA2 and psbA3 promoters, particularly in the -35 element, which is identical in psbA2 and psbA3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression analyses have led us to conclude Jansson, 1989,1991;Mohamed et al, 1993) that the -35 and -10 motifs of psbA2 constitute a strong light-inducible promoter in Synechocystis sp 6803. No expression of thepsbA7 gene has been detected (Mohamed and Jansson, 1989), and alignment of the upstream regions of-the three psbA genes (Figure 2) has shown that the two putative psbA 7 promoters (Osiewacz and Mclntosh, 1987;Mohamed et al, 1993;Nixon and Jansson, 1996) differ significantly from the psbA2 and psbA3 promoters, particularly in the -35 element, which is identical in psbA2 and psbA3.…”
Section: Resultsmentioning
confidence: 99%
“…Because psbA2 is highly expressed under normal growth conditions (Mohamed and Jansson, 1989), we first tried to activate the psbAl gene by engineering -35 and -10 promoter elements identical in The psbA7 sequence is from Osiewacz and Mclntosh (1987), the psbA2 sequence is from Mohamed et al (1993), and the psbA3 sequence is from Metz et al (1990) and Mohamed et al (1993). Distances are given relative to the ATG start codon (italics).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MED134 (6). The drop in PR content during the stationary phase may be in part due to the promoter we selected, because it is known that psbA2 expression and transcript stability are light-intensity dependent (68)(69)(70)(71)(72)(73), and so is heterologous expression driven by this promoter (74,75). It is worth noting that several of the recently discovered proteorhodopsins in 'chemotrophic', often psychrophilic, bacteria only contribute detectably to growth rate or cell yield when the cells are stressed and/or in stationary phase (6,(14)(15)(16)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%